2023
DOI: 10.1007/s10811-023-02973-6
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, intestinal morphology, blood biomarkers, and immune response of Thinlip Grey Mullet (Liza ramada) fed dietary laminarin supplement

Abstract: Laminarin is a source of immunostimulants and antioxidative biomolecules involved in supporting the performance and health of aquatic animals. Hence, this study investigated the growth performance, intestinal morphology, blood biomarkers, and immune response of Thinlip Grey Mullet (Liza ramada) fed dietary laminarin. For 60 days, mullets were fed diets supplemented with laminarin at 0, 200, 400, 600, and 800 mg kg−1, then the growth performance was evaluated, and samples were collected. The FBW, WG, SGR, PER, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…In this study, the supplementation of 0.8% laminarin significantly increased the intestinal amylase and trypsin activities of spotted seabass. The results are comparable with those of Abdel-Mawla et al, who stated found that dietary supplementation of 338-761 mg kg -1 laminarin enhanced the digestive enzyme activity of Liza ramada (Abdel-Mawla et al, 2023). At the same time, the results of this study were consistent with the results of growth performance, indicating that an appropriate amount of laminarin can enhance digestive enzyme secretion and improve nutrient digestion and absorption in spotted seabass, thereby promoting their growth.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, the supplementation of 0.8% laminarin significantly increased the intestinal amylase and trypsin activities of spotted seabass. The results are comparable with those of Abdel-Mawla et al, who stated found that dietary supplementation of 338-761 mg kg -1 laminarin enhanced the digestive enzyme activity of Liza ramada (Abdel-Mawla et al, 2023). At the same time, the results of this study were consistent with the results of growth performance, indicating that an appropriate amount of laminarin can enhance digestive enzyme secretion and improve nutrient digestion and absorption in spotted seabass, thereby promoting their growth.…”
Section: Discussionsupporting
confidence: 91%
“…There are few studies on aquatic animals. Abdel-Mawla et al (2023) found that dietary laminarin can improve intestinal villi morphology and increase the number of goblet cells in Liza ramada. This is The data presented are expressed as mean ± standard deviation (n=3).…”
Section: Figurementioning
confidence: 96%
See 2 more Smart Citations
“…These epithelial cells assist in the production of IgA through the activation of T cells and B cells that play a defensive role against various antigens [181]. Dietary Laminaria digitata (Phaeophyceae) and Gracilaria gracilis (Rhodophyta) significantly boosted the intestinal acid goblet cells of mullet (Liza ramada) [182] and European seabass (D. labrax) [183,184], which perform key roles in intestinal immune activity. Goblet cells act as a protector of intestinal barriers through the production and secretion of mucus and antimicrobial proteins (chemokines and cytokines), enhancing the local immune response of the intestine [185].…”
Section: Intestinal Morphologymentioning
confidence: 99%